2013
DOI: 10.1590/s0004-28032013000200037
|View full text |Cite
|
Sign up to set email alerts
|

Lung and Liver Changes Due to the Induction of Cirrhosis in Two Experimental Models

Abstract: -Context -To evaluate lung and liver changes in two experimental models using intraperitoneal carbon tetrachloride (CCl 4 ) and bile duct ligation (BDL). Methods -Twenty-four male Wistar rats were divided into a control group (CO) and an experimental group (EX). We evaluated the liver transaminases (AST, ALT, AP), arterial blood gases (PaO 2 , PCO 2 and SpO 2 ) and lipid peroxidation by TBARS (substances that react to thiobarbituric acid) and chemiluminescence. We also evaluated the antioxidant enzyme supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Ferrari et al[40] demonstrated that rats with cirrhosis, whether induced by BDL or by CCl 4 , exhibit necrosis, fibrotic nodules, inflammatory infiltrate and cellular changes. Tieppo et al[14] also observed that rats subjected to BDL exhibit hepatic changes with ductular proliferation and fibrosis, findings that improved in cirrhotic rats treated with quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrari et al[40] demonstrated that rats with cirrhosis, whether induced by BDL or by CCl 4 , exhibit necrosis, fibrotic nodules, inflammatory infiltrate and cellular changes. Tieppo et al[14] also observed that rats subjected to BDL exhibit hepatic changes with ductular proliferation and fibrosis, findings that improved in cirrhotic rats treated with quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high level of ROS may decrease the bioavailability of NO and lead to the constriction of pulmonary vessels [19]. Taken together, all these suggested mechanisms cannot be linked directly to POPH because of lacking an accepted animal model for POPH, and some limitations in human studies [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although, POPH can be linked to portal hypertension, the increase in portal pressure by partial mechanical obstruction of the portal vein in animals does not lead to pulmonary hypertension [33]. In addition, the increase of pulmonary artery pressure following the injection of sephadex microsphere into the portal vein [22], creation of portosystemic shunt [21] and intraperitoneal administration of carbon tetrachloride [20] could not entirely create a condition like POPH in human.…”
Section: Introductionmentioning
confidence: 99%
“…Although, POPH can be linked to portal hypertension, the increase in portal pressure by partial mechanical obstruction of the portal vein in animals does not lead to pulmonary hypertension [33]. In addition, the increase of pulmonary artery pressure following the injection of sephadex microsphere into the portal vein [22], creation of porto-systemic shunt [21] and intraperitoneal administration of carbon tetrachloride [20] could not entirely create a condition like POPH in human.…”
Section: Introductionmentioning
confidence: 99%